Investor's Fortune and Unit Trust Ratings - Ahmad Ridhuwan, Abdullah (2011)
This study examines the usefulness of rating information supplied by Lipper using a sample of 68 Malaysian unit trust funds from December 2000 to November 2010. Four performance measures were used namely the Sharpe ratio, Treynor ratio, Jensen's alpha, and Fama and French 3-factor model. Overall, the study provides evidence unit trusts underperformed the market index and risk free rate in 3-year, 5-year, and 10-year investment horizons except for the highest rated funds which were able to provide positive returns. The test on performance differential between funds in each rating categories shows that the highest rated funds, second to highest and third to highest significantly outperformed the lowest rated funds especially in a longer investment horizons. This result indicated that Lipper rating system is rather useful in identifying the lowest to highest performance funds.